2019
DOI: 10.3389/fpls.2019.01148
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Medicago MtCDFd1_1 Causes Delayed Flowering in Medicago via Repression of MtFTa1 but Not MtCO-Like Genes

Abstract: Optimizing flowering time is crucial for maximizing crop productivity, but gaps remain in the knowledge of the mechanisms underpinning temperate legume flowering. Medicago, like winter annual Arabidopsis, accelerates flowering after exposure to extended cold (vernalization, V) followed by long-day (LD) photoperiods. In Arabidopsis, photoperiodic flowering is triggered through CO, a photoperiodic switch that directly activates the FT gene encoding a mobile florigen and potent activator of flowering. In Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
(101 reference statements)
2
15
0
Order By: Relevance
“…However, in this mutant the delay in flowering is only moderate and could be explained by the reduction in MtFTa1 expression, suggesting that the disruption of both the MtFTb genes had little effect on flowering. This is consistent with previous flowering time observations when overexpression of MtCDFd1_1 also disrupted expression of both MtFTb genes, but the late flowering observed was dependent on loss of MtFTa1 function (Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in this mutant the delay in flowering is only moderate and could be explained by the reduction in MtFTa1 expression, suggesting that the disruption of both the MtFTb genes had little effect on flowering. This is consistent with previous flowering time observations when overexpression of MtCDFd1_1 also disrupted expression of both MtFTb genes, but the late flowering observed was dependent on loss of MtFTa1 function (Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the expression of FT-like genes are significantly reduced in LATE1 ( Psgi ) mutants ( Hecht et al, 2007 , 2011 ) and a dominant late flowering pea CDF mutant was recently shown to act in the same pathway ( Ridge et al, 2016 ). Similarly, in M. truncatula overexpression of the MtCDFd1_1 gene resulted in late flowering relative to wild type plants in LD photoperiods resulting in the plants flowering in a day-neutral manner ( Zhang et al, 2019 ). In addition, in both pea and M. truncatula , homologs of PHYA strongly promote flowering in LD with Mtphya mutants having strongly reduced levels of the LD-induced FT-like genes ( Weller et al, 2001 , 2004 ; Jaudal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MtCML42 was induced by cold but was reduced by ABA treatment, indicating the coldinduced MtCML42 expression was not associated with ABA. Among the large number of CMLs found in plant species a few CMLs are known to be expressed in response to cold, such as AtCML24 (Delk et al, 2005), CsCML16, CsCML18-2 and CsCML42 (Ma et al, 2019), ShCML44 (Munir et al, 2016) and MtCML40 (Zhang, Jiang, et al, 2019). The role of MtCML42 in the regulation of cold tolerance was documented in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…The results suggest that MtCML42 positively regulates cold tolerance. A few CMLs, such as AtCML10 (Cho et al, 2016), AtCML37 (Scholz et al, 2015) and ShCML44 (Munir et al, 2016), positively regulate cold, drought and salinity tolerance, whereas other CMLs, such as AtCML9 (Magnan et al, 2008), AtCML20 (Wu et al, 2017), AtCML42 (Vadassery et al, 2012 and MtCML40 (Zhang, Jiang, et al, 2019), negatively regulate abiotic stress tolerance. The positive or negative regulation of CMLs on abiotic stress tolerance is associated with jasmonic acid (Scholz et al, 2015;Vadassery et al, 2012;Zhu, Robe, et al, 2017) or ABA signaling (Delk et al, 2005;Magnan et al, 2008;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation